PERKEMBANGAN OLAHRAGA DI INDONESIA: TRANSFORMASI DARI TRADISI LOKAL HINGGA SISTEM KEOLAHRAGAAN MODERN - Sofia Theodora Purba; yeni fitria; Kristian Kevin Chanra Simatupang; Siti Ramalomohati Harahap; Michael Christiano Sitinjak; Wilson Situmorang; Regita Cahyani Zahra; Hotma K Gultom; Putra Arima; Irwansyah Siregar (STKIP Subang, 2026)
This study explores the historical evolution of sports in Indonesia, tracing their transformation from traditional cultural practices to a modern national sports system. The research aims to identify key developmental phases, analyze contributing sociocultural and political factors, and assess the impact of modernization on sports participation and national identity. Using a qualitative descriptive method supported by literature review from academic journals, books, and policy documents, findings indicate that Indonesian sports have undergone significant institutional, infrastructural, and cultural advancements. The shift from indigenous games to competitive, organized sports has been shaped by colonial influence, national integration policies, and global sports trends. Modernization has improved sports governance, athlete development, and international achievements while simultaneously challenging the preservation of traditional sports. The study concludes that the development of sports in Indonesia is a dynamic and continuous process influenced by cultural heritage, government policy, and global interaction.